THE INTERNET AS PART OF MARKETING (REVISTA DE HUMANIDADES Y CIENCIAS SOCIALES Y MULTIDISCIPLINARIA, 2021)
The investigation of market in international level, competitive conditions, small relatively cycle ofproducts, more increased requirements of clients, political and economic developments andcontinuous technological development consist samples of the influential agents in taking decisionsmarketing as a result the development of science information with equipment level but also softwareso the changing conditions of business environment give new dimensions in operation of takingdecisions in marketing. The use of internet offers an essential help in the direction of a betterunderstanding and successful management of dangers that the professional engagement inenterprises that maintain or intend to transfer a part or the total of their activities to internet buyingsites involves. Τhe specific article in order to investigate of factors influence internet in environmentof marketing, the causes of activity internet in markets based on method of secondary researchwhich used for the collection data which collected from libraries, sources and data from the sameenterprises for the creation of basis bibliographic review. Followed the content analysis, exportconclusions for the use products from consumers and understanding results of the actionsmarketing. The main target of article is researching the influence of internet in action ofentrepreneurship.